An Exploratory Study on Mind Wandering, Metacognition, and Verbal Creativity in Chilean High School Students - Preiss, David D.; Ibaceta, Miguel; Ortiz, Dominga; Carvacho, Héctor; Grau, Valeska (Frontiers in Psychology, 2019)
The purpose of this study was to explore the relationship between mind wandering, metacognition and creativity in a sample of Chilean high school students. 228 secondary students took three self-report scales on mind wandering, metacognitive strategies and reading difficulties, two verbal creativity assessments, a test of fluid intelligence and a measure of attentional capacity. First, a correlational analysis was used to describe the relations between all variables. Then, a single multiple hierarchical regression was carried out to predict verbal creativity, including as predictors fluid intelligence, attentional capacity, reading difficulties, mind wandering, and metacognition. Finally, a three way moderation model was conducted. This particular model explored the moderating effect of attentional capacity and metacognition, combined, on the effect of mind wandering on verbal creativity. Only students with both high attention and high metacognition displayed a positive relationship between mind wandering and verbal creativity. Results suggest that a certain level of cognitive self-regulation must be set in place to find a relationship between the disposition to mind wander and verbal creativity. Verbal creativity does not spontaneously result from mind wandering but requires those self-regulatory habits that helps students to plan, control and regulate their behavior so they can create something that is both novel and adequate. The study has some limitations arising from the self-report nature of some of its measures, especially that of metacognition. Given the exploratory nature of this study, this is a result that calls for further research.